2021
DOI: 10.1136/bmjopen-2020-043336
|View full text |Cite
|
Sign up to set email alerts
|

The importance and availability of adjustments to improve access for autistic adults who need mental and physical healthcare: findings from UK surveys

Abstract: Objectives To investigate autistic people’s views on the importance and availability of adjustments to mental and physical healthcare provision. To explore whether specific categories of adjustments can be identified and to identify any differences in their importance and availability between mental and physical healthcare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
(32 reference statements)
8
29
0
Order By: Relevance
“…We used the SRS-2 to describe autism characteristics and to compare individuals with a formal and suspected diagnosis before inclusion as one group for analysis. Previous research using this PAT-A sample found no significant difference in autism characteristics between those with an autism spectrum diagnosis and those who suspected they were autistic or were awaiting diagnosis (Brice et al, 2021), which we confirmed in our own subsample of this dataset using the SRS-2 (t (377) = − 0.57, p = 0.5701). Therefore, we used a combined sample.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We used the SRS-2 to describe autism characteristics and to compare individuals with a formal and suspected diagnosis before inclusion as one group for analysis. Previous research using this PAT-A sample found no significant difference in autism characteristics between those with an autism spectrum diagnosis and those who suspected they were autistic or were awaiting diagnosis (Brice et al, 2021), which we confirmed in our own subsample of this dataset using the SRS-2 (t (377) = − 0.57, p = 0.5701). Therefore, we used a combined sample.…”
Section: Discussionsupporting
confidence: 83%
“…Table 1 shows sample demographic characteristics. There were no significant differences in key demographic variables, such as age, gender or autistic characteristics between responders and non-responders to this study (see Brice et al, 2021).…”
Section: Participantsmentioning
confidence: 69%
“…Barriers have also been described in the context of access to physical healthcare for autistic individuals, and include communication disconnect between practitioners and autistic individuals, the impact of sensory sensitivities, and practical issues associated with executive functioning (Mason et al, 2019 ). Additionally, findings are supported by a very recent survey study of 537 autistic adults that examined accessibility of physical and mental healthcare provision, and outlined similar barriers to care (Brice et al, 2021 ).…”
Section: Discussionmentioning
confidence: 54%
“…Adults with autism emphasised the importance and availability of key adjustments that could improve accessibility and acceptability of healthcare services. Brice et al 6 recently reported that these were the sensory environment, the clinical and service context, and clinician knowledge and understanding. Preferred sensory environments included rooms with smaller numbers of people and lower levels of noise and light.…”
Section: What Adjustments Do People With Autism Want?mentioning
confidence: 99%